FACTORS AFFECTING THE MARKETING SURPLUS OF WHEAT IN BAGHDAD PROVINCE USING THE REGRESSIVE ECONOMETRIC MODEL - Abdul-Hameed, S. M.; Kadhim, Zuhal R. Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research aims to study and identify the most important economic and social factors affecting the marketing surplus of wheat farms in Baghdad Province  for the agricultural season 2023 using the regressive regression model. The data were obtained through a questionnaire prepared for this purpose and the study relied mainly on the raw data of a random sample of a total of 150 wheat farmers in the province distributed over the various agricultural units of Baghdad Province. Results showed that the marketing surplus of the wheat in Baghdad province is sold through three channels; the first is marketing to the state by 57%, the second is marketing to wholesalers by 40%, and the third is marketing to brokers by 3%. Results also displayed that the marketing surplus of wheat crop in Baghdad is positively affected by a set of variables, namely the amount of production of the getter, the average selling price per ton, and the efficiency of marketing services, while the marketing surplus is related to wheat is negatively affected by variables of in-kind deductions, family consumption, and loss of harvest and collection. The study recommended the need for nutritional awareness for individuals in rationing wheat consumption from the farm, as well as encouraging the establishment of an efficient marketing system by governmental and non-governmental organizations to market wheat production.